Azerbaijan Republic : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This paper presents the Joint Staff Assessment on Azerbaijan Republic's Poverty Reduction Strategy. The incidence of poverty remains slightly higher among urban than rural households, and is associated with falling employment opportunities and earnings in the formal economy. Although Baku has the largest absolute number of urban poor, poverty incidence is highest in provincial towns. Setting up a system to monitor living standards has been a major achievement, but the monitoring of those standards for refugees and internally displaced persons has serious shortcomings.